MODERN HISTORIOGRAPHY OF RUSSIAN-CHINESE RELATIONS (2020-2023) - Biryukova K.V. (Вестник Брянского государственного университета)
China never ceases to assert itself as an economic and geopolitical leader. Against the background of a pandemic that imperiously intervened in our lives, a crisis in relations between Russia and the United States and a number of European countries, a gradual transition to a multipolar political world, Russian-Chinese relations are constantly developing. The study is historiographical in nature. The author considers some works of the last three years on China, Russian-Chinese diplomatic relations and foreign policy, geopolitical strategies and strategic partnership between the two countries. The field of study also includes individual persons significant for the development of Russian-Chinese relations and the spread of Christianity in China (Savva Lukich Vladislavich-Raguzinsky, Russian diplomat and plenipotentiary ambassador to China, and Russian missionary to China, participant 12 and Head of the 13th and 15th composition of the Russian Orthodox mission in Beijing, sinologist Archimandrite Palladium (Kafarov), Baron F.R. Osten Saquena, Catholic missionary Mateo Ripa). The author is also interested in topical studies that reveal the topic of Russian-Chinese relations in a socio-cultural and religious context. Relevant means research of the last three years (2020-2023). The study is fragmentary in nature, since the scope of the article does not allow for the full presentation of works on Russo-Chinese relations in political, socio-cultural and religious contexts.